Extracting Vitabiotic Pharmaceutical Substances from Berry Raw Materials: Optimization of Processes - Shkol’nikova M.; Bakin I.; Mustafina A.; Aleksenko L. (Техника и технология пищевых производств)
The research features new processing methods of extraction of active antibacterial components from Siberian berries. The paper describes the content of biologically active agents and antibacterial dynamics in blackcurrant (Ribes nigrum L.) and common sea buckthorn (Hippophae rhamnoides L.) extracts. The study involved an analysis of the bactericidal biologically active agents in the extracts. The experiment revealed the main effect and synergism of the principal components, i.e. flavonoids, tannins, and vitamin C. It also established the leading role of the phenolic substances (flavonoids, tannins, phenolic acids, and glycosides) in the antibacterial influence on cultures of some kinds of pathogenic, potentially pathogenic, and unwanted microflora. The authors revealed some regularities of useful substances extraction in the conditions of ultrasonic processing. The optical density indicator of extracts during extraction helped to establish the optimum parameters of the process: mash ratio – 1:15; ultrasonic exposure frequency – 22 kHz. The experiment determined the mass fraction of extractive substances and active components, as well as the values of extraction coefficients of the berry raw material. Tannins and vitamin C were more extractable than flavonoids. The research also touched upon the impact of ultrasonic processing on the acceleration of extraction. When processing water-alcohol solutions of the raw material by ultrasonic irradiation with an intensity of 2 W/cm2 and a frequency of 22 kHz, the extraction duration fell from 300 to 15–20 minutes before the comparable values of balance concentrations of extractives were reached, in comparison with the control samples.